The Influence of Motivation and Walfare on Employee Performance - Hosen, Hosen; Satoto, Eko Budi; Herlambang, Toni; Sanosra, Abadi; Qomariah, Nurul (Budapest International Research and Critics University, 2024)
Employee performance is an important thing in an organizational structure. Increasing competition makes all organizations or companies race to improve the performance of their employees. The purpose of this paper is to determine and analyze the impact of employee work motivation and employee welfare on the performance of village officials in the Eastern District of Probolinggo Regency. The data used in this research is primary data obtained through distributing questionnaires. The Pini research population was village officials in the Eastern District of Probolinggo Regency, taking 100 village officials as samples for this research. Data was obtained by distributing prepared questionnaires. This measuring instrument in the form of a questionnaire will be tested using validity and reliability tests. Descriptive statistics are used to determine respondents' descriptions. Hypothesis testing is also carried out to determine the impact of exogenous variables on endogenous variables. After carrying out the analysis, the result is that work motivation has an impact on employee performance, and the welfare received by employees also has a significant effect on the performance of village officials in the Eastern District of Probolinggo Regency.